Functional indicators of peripheral arterial stiffness in solid organ recipients (literature review) - M. M. Lysenko; I. Yu. Tyunyaeva; A. O. Shevchenko (Вестник трансплантологии и искусственных органов)
Increased arterial stiffness is an important preclinical indicator of cardiovascular dysfunction, arterial hypertension and target organ injury. This condition increases the risk of long-term adverse events. Solid organ recipients face multiple risk factors for cardiovascular complications due to transplant rejection, lifelong medication use and adaptive features of the transplanted organ. The review presents an analysis of the results of studies on the main functional indicators of peripheral arterial stiffness, as well as the potential effect of immunosuppressive therapy on indicators of vascular stiffness in solid organ recipients.